1982
DOI: 10.1002/1097-0142(19820915)50:6<1031::aid-cncr2820500602>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

CNS prophylaxis in acute lymphoblastic leukemia. Comparison of two methods a southwest oncology group study

Abstract: Children with acute lymphoblastic leukemia were randomized to one of two treatment options for CNS prophylaxis. All patients received intrathecal therapy over a one‐year period with methotrexate, hydrocortisone and cytosine arabinoside. One‐half of the patients also received 2400 rad cranial radiation over 2 1/2 weeks. There was no significant difference in CNS relapse rate, length of hematologic remission or survival between the two groups. No further CNS relapses have been observed for the last four years. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Previous studies also identified male sex as a risk factor for iCNS relapse. 8,20,64,65 Interestingly, outcome was worse for boys than girls on St Jude's Total XIII and ALL-BFM 90 protocols, despite a very low iCNS relapse rate for both sexes. [66][67][68] Splenomegaly, nodal enlargement, and hepatomegaly were each significant predictors of iCNS relapse in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also identified male sex as a risk factor for iCNS relapse. 8,20,64,65 Interestingly, outcome was worse for boys than girls on St Jude's Total XIII and ALL-BFM 90 protocols, despite a very low iCNS relapse rate for both sexes. [66][67][68] Splenomegaly, nodal enlargement, and hepatomegaly were each significant predictors of iCNS relapse in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3,7 Seeking greater efficacy of CNS-directed therapy, some investigators and cooperative groups have added IT cytarabine and/or corticosteroids to MTX in pursuit of additive benefit or synergy. 6,[8][9][10][11][12][13] However, investigations assessing the benefit of these drug combinations in vitro or in animal models in vivo are inconclusive, as results show both antagonism and synergy. [14][15][16][17][18] At the time the CCG 1952 phase 3 study was designed, the isolated CNS (iCNS) relapse rate among children with standardrisk (SR) and low-risk ALL treated with IT MTX on CCG protocols was 6% to 8%, representing one third of all relapses.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the established adverse effects of CNS prophylaxis in childhood ALL, it is reasonable to search for safer but still effective alternatives (Kean & Smith, 1986;Nesbit et al, 1981;Bleyer et al, 1985;Chessels, 1985;Komp et al, 1982;Rowland et al, 1984). Although the number of patients in the present retrospective study is small, the conclusions support the clinical impression that standard CNS-P in adults is essential, effective and well tolerated, with only subclinical sequelae, and there is no indication to replace it until a clearly superior alternative is found.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were grouped into 11 categories by randomized comparison. Table I gives details of the CNS‐directed treatments 11–56. Steroid use is given in supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%